Pentingnya Banner Dan Petunjuk Arah Sebagai Strategi Pemasaran Untuk Meningkatkan Visibilitas UMKM "Batik Broyo" - Sabela, Noverta Yustisia; Pudjoprastyono, Hery (Journal Of Human And Education (JAHE), 2024)
This research aims to enhance the visibility and accessibility of the Micro, Small, and Medium Enterprises (UMKM) "Batik Broyo" located in Pakal Village, Surabaya, through the creation and installation of banners and directional signs. In the competitive digital era, MSMEs often face challenges in terms of branding and marketing. This activity began with a survey to identify the main needs of MSME actors, which revealed a lack of clear visual identity. Next, an analysis was conducted to plan a design that aligns with the product characteristics and target market. The creation process involved using graphic design applications to produce attractive and informative promotional materials. The installation of banners and directional signs is carried out in strategic locations to ensure optimal visibility. The results of this activity are expected to enhance the appeal of "Batik Broyo," make it easier for consumers to find the business location, and support the growth and sustainability of MSMEs in the area. Thus, this activity not only provides a solution to the identity problem of MSMEs but also contributes to the development of the local economy and the preservation of batik culture as a traditional Indonesian heritage.